Media Perspectives for the 21st Century - James Curran (Routledge, 2011)
We live in an era of continuous change to our communications environment. The communications landscape has never been static but the scale of contemporary change has been almost global due to the extensive use of new technologies and the implementation of market-led, neo-liberal policies. Communication and media studies need to change when the media change. This also helps explain the fact that communication studies are often in ‘crisis’ and under constant scrutiny. Even if communication and media studies are able to respond to what is happening in the communications sector and with media audiences, there is no one-to-one correspondence between the external conditions and the content of communication and media studies. Studies are dependent on what actually happens in the communications environment, yet communication (and in effect social) phenomena are always open to interpretation and rival theorization. A look back over the last three decades reveals an explosion in the development of communication technology. In contrast to the past, the new developments are shaping a communications landscape that differs greatly from what we were familiar with (Wang and Servaes, 2000: 1). We have seen a movement away from the dominance of print mass media to the prevalence of audiovisual media and, most recently, a transformation of the media towards the development of integrated and digitized communication technologies which are creating a more complex multimedia environment. This development has blurred the traditional frontiers between reading and writing and between communications based on audiovisual images and communications based on text. In effect, the continuous developments of the new media (Internet, online communication and mobile technology) have differed from the old media in a number of ways, such as in the production, distribution and reception of media content. The problem is that old media like newspapers and magazines do not have an audience problem – newspaper websites are a vital and growing source of news – but they do have a consumer problem. Similarly, although nowadays some refer to audiences as users or consumers (Pavlik, 1998), media studies cannot take the concept of ‘audience’ as a redundant academic device (Ruddock, 2008).